COVID-19 in vaccinated adult patients with hematological malignancies: preliminary results from EPICOVIDEHA - Pagano, Livio; Salmanton-García, Jon; Marchesi, Francesco; López-García, Alberto; Lamure, Sylvain; Itri, Federico; Gomes-Silva, Maria; Dragonetti, Giulia; Falces-Romero, Iker; van Doesum, Jaap; Sili, Uluhan; Labrador, Jorge; et al. (Blood, 2022)
In a Plenary Paper, Mittelman and colleagues assess the relative clinical efficacy of mRNA vaccination on COVID-19 disease incidence and outcomes in patients with hematologic malignancies compared with healthy matched controls. This population-based study from Israel links prior observations of poor serologic responses to vaccination to higher risk for breakthrough infection, hospitalization, and death in patients with blood cancer, especially those on active antineoplastic therapy. In an accompanying Letter to Blood, Pagano et al provide supportive data using a multination survey approach to capture outcomes for COVID-19 in vaccinated patients with hematologic neoplasms. They also emphasize the higher risk among patients with lymphoid malignancies. Together, these findings argue for both continued deployment of booster programs and ongoing public health guidance for this vulnerable group.
Keywords: Humans; 2019-nCoV Vaccine mRNA-1273; Hematologic Neoplasms; vakcína BNT162; lidé středního věku; Female; Aged; dospělí; senioři; lidé; hematologické nádory; Adult; COVID-19; ženské pohlaví; Male; BNT162 Vaccine; Middle Aged; Aged, 80 and over; vakcína firmy Moderna proti COVID-19; senioři nad 80 let; mužské pohlaví; SARS-CoV-2